Prevalence of Electrocardiographic Changes in Patients with Traumatic Brain Injury: A Prospective Hospital-based Study - Hamila, Mohamed; Hussein, Khaled; Ismail, Mohamed Fatehy; Kamal, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Head trauma and traumatic brain injury (TBI) are major causes of death and disability worldwide. TBI is associated with a variety of electrocardiographic (ECG) changes. AIM: We aimed to evaluate the prevalence of ECG changes in TBI. METHODS: Participants with TBI were included in the study, while participants with chest trauma or cardiovascular diseases were excluded from the study. A consecutive sample of 50 participants (mean age 37.8 ± 14.85 years, 80% males) was selected and referred for 12 lead ECG on admission, 24 h, and 72 h after admission. RESULTS: The prevalence of sinus bradycardia versus sinus tachycardia, short PR interval, ST segment elevation, and inverted T wave in the study population was 18% versus 38%, 26%, 2%, and 16% in ECG on admission, 5% versus 22%, 14%, 0%, and 10% in ECG 24 h after admission, 5% versus 8%, 4%, 0%, and 8% in ECG 72 h after admission, respectively. Serial ECG was significantly associated with changes in heart rate (χ² [1] = 17.337, p = 0.002) and short PR interval (χ² [1] = 9.695, p = 0.008), respectively. There was a significant association between ECG changes and brain edema (χ² [1] = 4.131, p = 0.042), intracerebral hemorrhage (χ² [1] = 4.539, p = 0.033), and subarachnoid hemorrhage groups (χ² [1] = 5.889, p = 0.015), respectively. CONCLUSIONS: ECG changes are prevalent in non-cardiac TBI patients. The significant association of serial ECG with changes in heart rate and short PR interval and the significant association of ECG changes with brain edema, intracerebral hemorrhage, and subarachnoid hemorrhage highlights the potential role of serial ECG as a screening tool for cardiac dysfunction in patients with TBI.